Fungal community composition in arthropogenically-active and non-active northern Borneo caves - IBRAHEM GHANI, WASTI; TOM M., FAYLE; Jayaraj Vijaya, Kumaran; Faisal Ali, Anwarali Khan; Jaya Seelan, Sathiya Seelan (Malaysian Nature Society, 2024)
Fungal studies are scant within this region of Borneo, and the potential effects of anthropogenic disturbance on fungal communities in Sabahan caves have not been explored. This study involved opportunistic sampling of guano, speleothems, and cavern water from four caves in Sabah, Malaysia, categorised according to the level of anthropogenic activity. The dilution method was used for fungal isolation and abundance calculations. Morphological identification of axenic cultures was conducted, and DNA barcoding of the ITS region of cryptic species corroborated identification. A total of 170 axenic cultures were attained, composed of 69 morphological taxonomic units (MTUs), 33 genera, ten orders, and two divisions – Ascomycota and Basidiomycota. Fifty-seven of the 69 MTUs were identified to the species level. The genera Aspergillus and Penicillium were particularly prevalent, with a combined total of 86 isolations (50.6%). Notably, twelve species were documented for the first time in cave ecosystems of Sabah. The average fungal abundance across all substrates and fungal taxa occurrence was found to be higher in samples found in active caves. A significant difference in relative abundance was observed between active and non-active cave conditions. Beta regression modelling indicated that anthropogenic activity is a significant factor influencing the composition of cave fungal communities. While anthropogenic activity seems to affect cave mycobiomes, especially by selecting for ubiquitous fungi, it is likely not the sole influencing determinant of their composition.